Systemic inflammatory regulators and preeclampsia: a two-sample bidirectional Mendelian randomization study - Li, Chu; Tian, Yishu; Dougarem, Djouhayna; Sun, Litao; Zhong, Zixing (Frontiers in Genetics, 2024)
Background: Systemic inflammatory regulators have been associated with preeclampsia (PE) during pregnancy; however, there is inconsistent evidence from animal models and observational results. Methods: Using summary data from genome-wide association studies (GWASs), we performed a bidirectional Mendelian randomization (MR) analysis of two samples of systemic inflammatory regulators (n = 8,186) and PE (n = 267,242) individuals of European ancestry. As our primary analysis, we used the random-effects inverse-variance weighted (IVW) approach. Sensitivity and pleiotropy analyses were conducted using the MR–Egger method, weighted median, MR Pleiotropy RESidual Sum and Outlier (MR-PRESSO), and Cochran’s Q test. Results: The results indicate that there is a correlation between a higher circulating level of tumor necrosis factor alpha (TNF-α) and interleukin-9 (IL-9) and an increased risk of PE (odds ratio [OR] = 1.32, 95% confidence interval [CI] = 1.09–1.60, p = 0.004 and OR = 1.28, 95% CI: 1.02–1.62, p = 0.033, respectively). Conversely, lower levels of stem cell growth factor beta (SCGF-β) (OR = 0.89, 95% CI: 0.80–0.99, p = 0.027) and interleukin-5 (IL-5) (OR = 0.80, 95% CI: 0.65–0.98, p = 0.030) are linked to an increased risk of PE. The macrophage migration inhibitory factor (MIF) is the downstream inflammatory regulator of PE, according to reverse magnetic resonance imaging studies. Conclusion: Our study suggests that SCGF-β, IL-5, IL-9, and TNF-α causally affect the PE risk, while PE is causally associated with MIF. Further studies are needed to validate these biomarkers in managing PE.